INSPANNING VERBINTENIS DALAM TINDAKAN MEDIS YANG DIKATEGORIKAN SEBAGAI TINDAKAN MALPRAKTEK - Fayuthika Alifia Kirana Sumeru; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2022)
Article 28 of the 1945 Constitution states that one of the rights that every human being must have is health. So that in its implementation it provides efforts in the form of health to the community through the provision of appropriate health services. However, medical actions performed by doctors can lead to 2 categories, namely: Inspanning Verbintenis (seek results) and Resultaat Verbintenis (promising results). Inspanning Verbintenis is an agreement or agreement to make maximum efforts in carrying out what has been agreed, while Resultaat Verbintenis is an agreement that will provide concrete results, namely in accordance with what has been agreed. It should be understood that before taking medical action, the patient has the right to know information about the medical action to be carried out which in this case has been regulated in the Regulation of the Minister of Health. It is known that the general public only knows the results, but the actions taken by doctors do not rule out the possibility of producing results that may not be in accordance with the patient's wishes. As well as medical actions that have been appropriate, but in fact cause reactions that may be referred to as malpractice actions due to the results of the reaction to the medical action given.